Progranulin autoantibodies in systemic sclerosis and autoimmune connective tissue disorders: A preliminary study. Issue 4 (10th September 2019) - Klemm, Philipp; Assmann, Gunter; Preuss, Klaus‐Dieter; Fadle, Natalie; Regitz, Evi; Martin, Thierry; Pfreundschuh, Michael; Thurner, Lorenz
Abstract: Objective: The present study aimed to investigate progranulin autoantibodies in systemic sclerosis and autoimmune connective tissue disorders. Progranulin is a physiologic tumor necrosis factor (TNF) antagonist. Progranulin antibodies decrease progranulin levels. Methods: Serum samples of 123 patients with systemic sclerosis and various autoimmune connective tissue disorders (Sjoegren's syndrome [SjS], mixed connective tissue disorder, polymyositis [PM] and dermatomyositis [DM], antiphospholipid syndrome [APLS], and undifferentiated connective tissue disease [UCTD]) were tested for progranulin antibodies using enzyme‐linked immunosorbent assay. Results: Progranulin antibodies were found in 34 of 123 (27.6%) patients at least once during their disease. In detail, 2 of 8 (25%) patients with limited cutaneous systemic sclerosis, 10 of 31 (32.3%) patients with diffuse cutaneous systemic sclerosis, 9 of 22 (40.9%) patients with SjS, 1 of 3 (33.33%) patients with mixed connective tissue disease, 4 of 33 (12.1%) patients with DM or PM, 6 of 15 (40%) patients with APLS, and 2 of 11 (18.2%) patients with UCTD were positive for progranulin antibodies during the course of disease. Conclusions: Progranulin antibodies are frequently present in patients with systemic sclerosis and other autoimmune connective tissue disorders. Despite the lack of specificity for a given autoimmune disease, progranulin antibodies might not only indicate a potential subtype but also play a pathogenic role in patients with autoimmune connective disorders. Given the important role of TNF‐α in inflammatory processes in autoimmune connective tissue disorders, progranulin antibodies might support the proinflammatory environment by neutralizing the TNF blocker progranulin. Abstract : We first report progranulin autoantibodies, that have a pathological role, in systemic sclerosis and other autoimmune connective tissue disorders. Progranulin antibodies decrease progranulin levels, a physiological tumor necrosis factor (TNF) antagonist, and thus enhance an inflammatory environment.